THE IMPLEMENTATION OF INTERACTIVE MODEL TO TEACH DESCRIPTIVE TEXT IN READING TO THE DEPARTMENT OF TEACHERS TRAINING - Marnala Pangaribuan; Carolina Pakpahan (Jurnal Darma Agung, 2022)
The goal of this study is to develop an interactive approach to teach descriptive text in reading to the teacher training department. The author employed both quantitative and qualitative research approaches in this study. The data was collected through observations, tests, paper sheets, and teacher conversations during the teaching and learning process. This study's participants will be lecturers from the Fourth Semester Student English Department of Teachers Training. This research takes place in the Fourth Semester Student English Department of Teachers Training. This research makes use of both quantitative and qualitative data. The quantitative data gathered by computing the reading test scores. Observation, questionnaire sheets, and interviews will be used to collect qualitative data. The quantitative data from the data KKM of English subject in the school was 70 as a result of this research, the mean of assessment descriptive text is 76, and the pupils received 6 points more than the KKM grade. The qualitative data collected and analyzed through the observation sheet, interviews, and questionnaires revealed that students are engaged, active, and excited about the learning process Interactive model. The interactive concept was skillfully applied by the teacher with the students.